Co-crystallization of Keggin type polyoxometalates [HL]3[PW12O40] and [Ln(DMF)8][PW12O40] (Ln = La, Dy, Yb) (L = N-(2-hydroxyphenyl)-3-methoxy-salicylideneamine): Syntheses, structures and magnetic properties. (28th January 2016) - Saha, Sudeshna; Jana, Partha P.; Gómez-García, Carlos J.; Harms, Klaus; Nayek, Hari Pada
Graphical abstract: Four new Keggin type polyoxometalate clusters [HL]3 [PW12 O40 ]·5MeOH (1 ) and [Ln(DMF)8 ][PW12 O40 ] Ln = La (2 ), Dy (3 ), Yb (4 ) (L = N -(2-hydroxyphenyl)-3-methoxy-salicylideneamine) have been synthesized. All complexes are characterized by standard analytical techniques and their magnetic properties have been investigated. Abstract: Four new Keggin type polyoxometalate clusters [HL]3 [PW12 O40 ]·5MeOH (1 ) and [Ln(DMF)8 ][PW12 O40 ] Ln = La (2 ), Dy (3 ), Yb (4 ) (L = N -(2-hydroxyphenyl)-3-methoxy-salicylideneamine) have been synthesized. Co-crystallization of complex1 with each of the three complexes2 –4 takes place when the Schiff base ligand is treated with hydrated phosphotungstic acid, H3 [PW12 O40 ]· x H2 O, hydrated lanthanide nitrate, Ln(NO3 )3 ·6H2 O in the presence of Ni(NO3 )2 ·6H2 O. The Schiff base ligand is protonated in complex1 and thus it is neutralizing the charge of the polyoxotungstate anion, [PW12 O40 ] 3 − . A dimethylformamide (DMF) coordinated trivalent lanthanide ion balances the negative charge of the polyoxoanion in2 –4 . All complexes are characterized by several standard analytical techniques. Solid state molecular structures of1 –4 were confirmed by single crystal X-ray diffraction analyses. The magnetic properties of complexes3 and4 confirm the presence of monomeric Dy(III) and Yb(III) complexes with a thermal depopulation of the highest energy Stark levels as the temperature is decreased.